Flurbiprofen alone and in combination with alfuzosin for the management of lower urinary tract symptoms - Gokkaya, Cevdet Serkan (Cent European J Urol, 2015)
INTRODUCTION: We aimed to investigate the effectiveness and safety of flurbiprofen, a non-steroidal anti-inflammatory drug with dual cyclooxygenase inhibition, and α-blocker alfuzosin, both alone and in combination with each other for lower urinary tract symptoms suggestive of benign prostatic obstruction (LUTS/BPO). MATERIAL AND METHODS: Ninety patients complaining of moderate-to-severe LUTS/BPO were randomly assigned into 3 groups (30 patients each) to receive alfuzosin XL 10 mg, or flurbiprofen SR 200 mg, or combination of alfuzosin XL 10 mg and flurbiprofen SR 200 mg, once daily for 4 weeks. Patients were evaluated using the international prostate symptom score (IPSS) (total and IPSS(storage), IPSS(empty) subscores), uroflow-metry (maximum (Q(max)) and average (Q(ave)) flow rates) and postvoid residual urine (PVR) both at baseline and following the drug therapy course. RESULTS: There was no difference among the 3 groups regarding age and baseline values of prostate volume, IPSS, IPSS(storage), IPSS(empty), Q(max), Q(ave) and PVR (P >0.05). IPSS, IPSS(storage), IPSS(empty), and PVR decreased significantly in all the 3 groups after drug therapies (P <0.01). However, Q(max) and Q(ave) significantly improved only in the combination group (P <0.01). CONCLUSIONS: Addition of flurbiprofen increased the therapeutic effectiveness of alfuzosin by further improving symptoms in patients with LUTS/BPO. Combination therapy also improved urine flow compared to baseline. Monotherapy with flurbiprofen was not superior to alfuzosin.